2020
DOI: 10.31890/vttp.2020.05.13
|View full text |Cite
|
Sign up to set email alerts
|

Pathomorphological changes in individual tubular and parenchymal organs of quails according to eimeriosis

Abstract: The work is devoted to the study of pathologic-anatomical and microscopic changes in tubular (duodenum, jejunum, cecum) and parenchymal (liver, lungs, spleen, kidneys) organs of quails for eimeriosis caused by E. tenella, E. necatrix, E. acervulina. The work was carried out on the basis of the pathomorphological laboratory of the Department of anatomy and histology of Zhytomyr national agroecological University (Zhytomyr, Ukraine).Average invasion intensity after E. tenella, E. necatrix, E. acervulina was 4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(14 reference statements)
1
0
0
Order By: Relevance
“…The damage inflicted by Eimeria spp. on the surface layers of the mucous membrane, leading to exudative processes involving lymphoid structures and exhibiting manifestations of hyperplasia, lends support to pathological anatomical changes in the intestines of pigeons with experimental eimeriosis (Liulin et al, 2021) and data reported by Kot et al (2020), where eimeriosis serous-catarrhal, catarrhal-mucous-hemorrhagic enteritis and necrosis of the intestinal mucosa were detected in quails. Furthermore, parallels in these changes are evident in chickens subjected to experimental infection with Eimeria maxima, Eimeria tenella, Eimeria necatrix, and Eimeria acervulina.…”
Section: Discussionsupporting
confidence: 79%
“…The damage inflicted by Eimeria spp. on the surface layers of the mucous membrane, leading to exudative processes involving lymphoid structures and exhibiting manifestations of hyperplasia, lends support to pathological anatomical changes in the intestines of pigeons with experimental eimeriosis (Liulin et al, 2021) and data reported by Kot et al (2020), where eimeriosis serous-catarrhal, catarrhal-mucous-hemorrhagic enteritis and necrosis of the intestinal mucosa were detected in quails. Furthermore, parallels in these changes are evident in chickens subjected to experimental infection with Eimeria maxima, Eimeria tenella, Eimeria necatrix, and Eimeria acervulina.…”
Section: Discussionsupporting
confidence: 79%